2003
DOI: 10.1345/aph.1c196
|View full text |Cite
|
Sign up to set email alerts
|

Topical Corticosteroid Prescribing Patterns following Changes in Drug Benefit Status

Abstract: Prescribing of topical corticosteroid combination products in Nova Scotia decreased following the formulary revision. There was an increase in potent topical corticosteroid prescribing. Future study involving evaluation of patient outcomes would be useful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…This may be explained by the fact that the portion of the 24 therapeutic classes of the total pharmaceutical expenditure was relatively small (2.1%), weakening the effect, although expenditures decreased for some drugs. These results are consistent with the findings of Soumerai et al, who analyzed data on claims from New Jersey Medicaid patients after the removal of drugs in 12 categories from the reimbursement listing and found that excluded drugs accounted for 7% of total drug use but that the delisting of these drugs did not have a significant negative effect on the total pharmaceutical expenditure [4].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This may be explained by the fact that the portion of the 24 therapeutic classes of the total pharmaceutical expenditure was relatively small (2.1%), weakening the effect, although expenditures decreased for some drugs. These results are consistent with the findings of Soumerai et al, who analyzed data on claims from New Jersey Medicaid patients after the removal of drugs in 12 categories from the reimbursement listing and found that excluded drugs accounted for 7% of total drug use but that the delisting of these drugs did not have a significant negative effect on the total pharmaceutical expenditure [4].…”
Section: Discussionsupporting
confidence: 91%
“…Campbell et al concluded that prescriptions for a topical corticosteroid combination drug decreased after its exclusion [4] and that the restriction of meperidine eliminated the user of analgesic meperidine [5]. On the other hand, Kreling demonstrated an increase in the total drug expenditure by the restriction of analgesics [6].…”
Section: Introductionmentioning
confidence: 99%
“…Among the 35 articles that satisfied the inclusion criteria, 11 –47 several general trends were observed. Most studies ( n = 18, 43.9%) had been carried out in one province, British Columbia.…”
Section: Resultsmentioning
confidence: 95%
“…Another study assessed the impact of the exclusion of selected topical corticosteroid products from the Nova Scotia formulary in 2000, after an evidence-based drug review of this therapeutic class found certain topical corticosteroids did not meet standards for inclusion (Campbell et al, 2003). Not surprisingly, use of certain topical corticosteroid products decreased after this change, as well as associated average costs.…”
Section: Box 4 Evidence Of the Impact Of Formulary Listing On Consumption Patternsmentioning
confidence: 99%